PERBANDINGAN KEMAJUAN PROGRES TAMBANG BATUBARA DI PT SAMANTAKA PADA BULAN JULI-AGUSTUS TAHUN 2021 DENGAN BULAN FEBRUARI-MARET TAHUN 2022 - Ristian Mades Vieri; Desi Syafriani; Dwi Arini; Defwaldi Defwaldi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Coal mining progress is a measurement activity that is carried out every day for as long as mining activities are carried out. The measurement of coal mining progress is carried out at the PT Samantaka mine which aims to determine the changes that occur in the mine, the progress of this mine is also carried out to determine the progress of the mine every month, both in knowing the land and remaining coal reserves and also to determine the coal production every month. the month. In addition, measuring mine progress is very important, because to find out the next mine design it is necessary to obtain a mine progress map first. Mine progress measurement to retrieve crees, toe, spot, floor and roof data. From this data, a map of mining progress and coal volume calculations can be obtained, volume calculations are usually carried out after the depiction is carried out, because volume calculations must obtain a 3D shape of coal for which volume will be calculated. The results of coal calculations are usually in the form of tonnage calculations. The results of the calculation of coal in 2021 in July and August there is a comparison of the volume of reserves with those in the stockpile is 908 tons and 2,883 tons, while in 2022 in February and March there is a volume comparison of 3,675 tons and 646 tons.